2019
DOI: 10.1177/0363546519883259
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Progressive Return to Activity Guidelines May Expedite Symptom Resolution After Concussion for Active Duty Military

Abstract: Background: Clinical recommendations for concussion management encourage reduced cognitive and physical activities immediately after injury, with graded increases in activity as symptoms resolve. Empirical support for the effectiveness of such recommendations is needed. Purpose: To examine whether training medical providers on the Defense and Veterans Brain Injury Center’s Progressive Return to Activity Clinical Recommendation (PRA-CR) for acute concussion improves patient outcomes. Study Design: Cohort study;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…11 Results suggested that this training had a significant positive impact on clinical practices as well as on patients' recovery from concussion. 27 Interview data and informal feedback indicated that the training was well received and impacted concussion clinical practices as intended. Quantitative results were even more compelling; compared with patients who received concussion treatment before providers received the PRA training, patients who were treated after provider training were 59% more likely to receive education from their providers, and they had lower levels of physical and vestibular activity during the first week of concussion recovery.…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 99%
See 4 more Smart Citations
“…11 Results suggested that this training had a significant positive impact on clinical practices as well as on patients' recovery from concussion. 27 Interview data and informal feedback indicated that the training was well received and impacted concussion clinical practices as intended. Quantitative results were even more compelling; compared with patients who received concussion treatment before providers received the PRA training, patients who were treated after provider training were 59% more likely to receive education from their providers, and they had lower levels of physical and vestibular activity during the first week of concussion recovery.…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 99%
“…25 As shown in Figure 1, concussed SMs in the DVBIC PRA study engaged in relatively low levels of activity (and high levels of rest) immediately after injury, followed by gradual increases in activity over the following 3 to 6 months, with an average increase in total activity of 63% over the full study time frame. 26,27 Physical, vestibular/balance, and military-specific activities increased most rapidly, whereas cognitive and lifestyle activities (i.e., reading, socializing, watching television) increased more slowly (Fig. 2).…”
Section: Changes In Neurobehavioral Symptoms and Activity Levels Acromentioning
confidence: 99%
See 3 more Smart Citations